Crowd evacuation simulation based on emotion contagion. (2018) - Du, Xuemei; He, Wu; Mao, Yan; Rao, Yunbo
Simulation study on evacuation scenarios has an important influence on public safety. Unfortunately, the traditional evacuation-drill approach for emergency situations focuses on the physiological interaction between individuals/crowds, whereas the approach ignores psychological interaction. In this paper, we present an emotion contagion model that associates components, such as physiological demand, security requirement and personality traits, with individual agents comprising a crowd, and produces emergent behaviours in the crowd as a whole. The emotion contagion model realises the interaction of physiological and psychological factors. Personality traits are associated with emotions by using the OCEAN, OCC and PAD models. To reflect the complexity of emotion contagion of crowd, we consider three processes: contagion, update, and decay. We also consider the effect of emotions on the movement. Testing results demonstrate that the proposed method is effective and realistic for simulating the movement of heterogeneous crowd in emergency situations.